2020
DOI: 10.1021/acs.jpcc.0c06883
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Stability of Free-standing and Metal-Supported Borophenes: Quantum Monte Carlo and Density Functional Theory Calculations

Abstract: Quantum Monte Carlo (QMC) and density-functional theory (DFT) calculations were carried out to study cohesion energetics of two-dimensional (2D) sheets of boron atoms called borophenes. Our QMC calculations confirmed the polymorphism among free-standing borophenes that was reported in previous DFT studies. Although Perdew–Burke–Ernzerhof (PBE) calculations significantly overestimate the cohesive energies of 2D boron sheets, DFT-PBE relative energetics with respect to each other among various free-standing boro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…We call this structure "the relaxed model", which is in agreement with several previous works. [14][15][16] However many stronger theoretical and experimental works suggest a closer interlayer distance (∼ 2 Å), and a covalent interlayer interaction for bilayer borophene. [17][18][19] Here, two important questions arise: Why the interlayer interaction should be covalent?…”
Section: A the Basic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We call this structure "the relaxed model", which is in agreement with several previous works. [14][15][16] However many stronger theoretical and experimental works suggest a closer interlayer distance (∼ 2 Å), and a covalent interlayer interaction for bilayer borophene. [17][18][19] Here, two important questions arise: Why the interlayer interaction should be covalent?…”
Section: A the Basic Modelmentioning
confidence: 99%
“…For instance, theoretical studies have suggested the interlayer distance of bilayer borophene in the range of 2.5 to 3 Å, suggesting a van der Waals (vdW) interaction between the layers. [14][15][16] However, the synthesized bilayer borophenes show a much closer interlayer distance, around 2 Å, implying relatively strong covalent bonds. 17,18 However, some theoretical studies considered some constraints to design the bilayer borophenes with similar interlayer distance to the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…One contender in the 2D materials that has attracted tremendous attention is borophene, [23][24][25][26][27][28][29][30][31][32][33][34] a single layer of boron. Because of the electron deficiency, borophene cannot have a normal hexagonal structure like graphene, but a boron atom is introduced at the center of the hexagonal structure, resulting in a triangle structure.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, this study utilizes density functional theory (DFT) , calculations benchmarked to diffusion Monte Carlo (DMC) calculations to examine the structural stability and binding nature of various Pt layers on a graphene substrate. DMC, which fully incorporates electron–electron correlations, has been used to provide quantitatively accurate descriptions of cohesion energetics and interlayer bindings for different 2D vdW systems. The accuracy from DMC benchmarking is important here because the mixture of chemical, metallic, and vdW binding is particularly challenging to describe within the DFT framework alone.…”
Section: Introductionmentioning
confidence: 99%